The Book of Nonsense - Lear, Edward, 1812-1888 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Book of Nonsense" by Edward Lear is a whimsical collection of nonsensical poetry and verse written during the mid-19th century. This charming book is renowned for its playful use of language and absurd characters, representing a key example of Victorian literature that celebrates imagination and humor. The likely topic of the book revolves around the various silly and amusing situations encountered by its eccentric characters. In "The Book of Nonsense," Lear presents a series of limericks, each featuring quirky individuals caught in ludicrous predicaments. These short verses introduce distinctive characters such as an old man with a beard who deals with birds making nests in it, a young lady with unusually long nose, and an old person whose actions lead to humorous consequences. The tone is light-hearted, with an emphasis on absurdity that entertains readers of all ages, making it a delightful exploration of human eccentricities and whimsical situations. Each poem elicits smiles through its clever rhymes and exaggerated scenarios, reflecting the enchanting spirit of nonsense literature. (This is an automatically generated summary.)
Release date is 1997-07-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Limericks, Juvenile; Children's poetry, English; Nonsense verses, English; Humorous poetry, English